Miscibility enhancement of poly(vinyl chloride)/polystyrene blend: Application to membrane separation of benzene from benzene/cyclohexane mixture by pervaporation. Issue 14 (21st September 2016) - Aouak, Taieb; Alghamdi, Abdulaziz Ali; Alrashdi, Ahlam Abdulrahman; Ouladsmane, Mohamed; Alam, Mohammad Mezbaul; AlOthman, Zeid; Naushad, Mu
ABSTRACT: In order to improve the miscibility of poly(vinyl chloride)/polystyrene (PVC/PS) system and to use the prepared material as a membrane to separate benzene from benzene/cyclohexane mixture by pervaporation technique, two poly(styrene- co -N-vinylpyrrolidone) (PSVP) copolymers containing 6.67 and 13.55 mol% of N-vinylpyrrolidone (N-VP) contents were synthesized through a radical polymerization. A comparative study of the miscibility of the PVC/PSVP blends with different compositions was carried out using differential scanning calorimetry, viscosimetry and Fourier transform infrared spectroscopy methods in which the interaction parameters between the two components were widely investigated. To improve the pervaporative flux of PVC membrane to separate benzene from benzene/cyclohexane mixture, a preliminary test of swelling and sorption was performed on PVC/PSVP7 membranes using an azeotropic benzene/cyclohexane mixture. It was revealed that the PVC/PSVP7 membrane containing 10 wt% of PSVP7 showed the best performance and the diffusion behaviour of this mixture through PVC and PVC/PCVP7 membranes has a Fickian behaviour. The pervaporation parameters of this membrane support those of the swelling and selective sorption data and reveal that this membrane could enhance the total flux without significantly affecting its selectivity to benzene.